'And now they have taken over': hobbyist and professional archaeologist encounters with the material heritage of the First World War in western Belgium. Issue 1 (2nd January 2022) - Thomas, Suzie; Deckers, Pieterjan
ABSTRACT: Since almost immediately after the fighting ended, the First World War (WWI) sites of conflict in Western Flanders, Belgium, have attracted attention from visitors and collectors. Heritage management questions came to the fore especially in the run-up to WWI's centenary years (2014–2018), and professional archaeologists representing the authorities in Flanders had already begun to take a greater interest in the war's archaeological remains. The activities of hobbyist amateurs, particularly metal detectorists, came under greater scrutiny. In this article, we explore the perspectives of local hobbyist enthusiasts and heritage professionals in the context of changing attitudes towards and values associated with the material heritage of the WWI in Western Flanders. We reflect upon the tensions that emerge when different interest groups clash, the disagreements between professional and amateur interests, and also upon the particular context of conflict heritage when there are numerous interests and stakeholders involved.